2018
DOI: 10.3126/ijasbt.v6i1.18795
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Level and Irrigation Interval on Mitigating Stemphylium Blight and Downy Mildew in Onion

Abstract: Field trial was conducted on horticultural farm of Lamjung Agriculture Campus, Lamjung, Nepal between December-April 2016/17 on onion (Allium cepa), following two factorial Randomized Block Design with three replications and fifteen treatments to assess disease severity of Stemphylium blight (Stemphylium vesicarium) and Downy mildew (Peronospora destructor). The onion cultivar Red Creole, widely grown in this locality and susceptible to these diseases was used for trial. The disease intensity for Stemphylium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
3
Order By: Relevance
“…The epidemics of downy mildew can be favored by excessive fertilization with soluble mineral fertilizers, especially nitrogen [8] . Studies conducted by Acharya & Shrestha [17] , revealed that nitrogen doses above 140% of the recommended ones can promote increased severity of downy mildew in onion plants. However, Gonçalves; Souza & Silva; Boff [9] observed no effect of mineral fertilization on downy mildew infestation for doses of N and K between the normal and up to three times the recommended.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemics of downy mildew can be favored by excessive fertilization with soluble mineral fertilizers, especially nitrogen [8] . Studies conducted by Acharya & Shrestha [17] , revealed that nitrogen doses above 140% of the recommended ones can promote increased severity of downy mildew in onion plants. However, Gonçalves; Souza & Silva; Boff [9] observed no effect of mineral fertilization on downy mildew infestation for doses of N and K between the normal and up to three times the recommended.…”
Section: Resultsmentioning
confidence: 99%
“…
We analyzed the relationship between nutrient (N and K) parceling and population density on the severity of onion downy mildew under no-tillage fertigation cultivation in the conditions of Alto Vale do Itajaí (Barzil). For this purpose, field trials were conducted in the years , 2018 and 2019. The treatments corresponded to four population densities (300, 400, 500 and 600 mil plants ha -1 ) subjected to applications of nitrogen (150 kg N ha -1 ) and potassium (127.5 kg K 2 O ha -1 ) distributed throughout the vegetative cycle of the crop via fertigation on a weekly, biweekly and monthly basis, based on the absorption curve of these nutrients for the cultivar Empasc 352-Bola Precoce.
…”
mentioning
confidence: 99%
“…As epidemias do míldio podem ser favorecidas pela adubação excessiva com fertilizantes minerais solúveis, em especial, do nitrogênio (WORDELL FILHO;BOFF, 2006). Estudos realizados por Acharya & Shrestha (2018), revelaram que doses de nitrogênio acima de 140% das recomendadas podem promover o aumento da severidade do míldio em plantas de cebola. No entanto, Gonçalves; Souza e Silva; Boff (2004) não observaram efeito da adubação mineral sobre a infestação de míldio para doses de N e K entre a normal e até três vezes a recomendada.…”
Section: Metodologiaunclassified
“…Dessa forma, a ausência de relação entre o parcelamento de nutrientes e a AACPD pode estar relacionada tanto à dose fornecida dos nutrientes, considerada baixa em relação as doses citadas por Acharya & Shrestha (2018) que podem promover o aumento da severidade do míldio, quanto, no caso do nitrogênio, à fonte utilizada (nitrato de amônio). Isso indica que a metodologia adotada permitiu que os nutrientes fossem fornecidos de forma a não interferir no processo doença.…”
Section: Metodologiaunclassified
See 1 more Smart Citation